Antimicrobial Activity and Identification of Antimicrobial Substances of Antagonistic Bacteria against Black Spot of Sweet Potato - Zhimin WANG; Jinling MA; Zhaoyong SUN; Yingying SHI; Dongyan LI; Jingying SHI (Shipin gongye ke-ji, 2023)
The losses of harvested sweet potato is large due to postharvest disease, among which black spot, caused by Ceratocystis fimbriata is one of the most important. In this study, the antimicrobial activities of Bacillus amyloliquefaciens (JK) and Klebsiella pneumoniae (GK) screened in the previous research with strong antagonistic effect on C. fimbriata were analyzed. The volatile antifungal components of the two antagonistic bacteria were analyzed by gas chromatography-ion mobility spectrometry (GC-IMS) and gas chromatography-mass spectrometry (GC-MS). It was found that fumigation sweet potato with fermentation of the two antagonistic bacteria delayed the onset time of black spot and effectively controlled the development of the disease spot. The volatile components were ketones, alkanes, alcohols, esters, aldehydes and so on. In all of them, 1-hexanol, 2-ethyl-, hexanal, 2-nonanone and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate had strong inhibitory effects on C. fimbriata by plate test. After the two safety gas components hexanal and 2-nonone were mixed in the ratio of 1:1, the growth of C. fimbriata could be completely inhibited when the concentration of the mixtures reached 200 µL/L. This study would provide a reference for the application of antagonistic microorganisms in postharvest fruits and vegetables.